2005
DOI: 10.1111/j.1365-2486.2005.001051.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of climatic change for water temperature and brown trout populations in Alpine rivers and streams

Abstract: Twenty-five years of extensive water temperature data show regionally coherent warming to have occurred in Alpine rivers and streams at all altitudes, reflecting changes in regional air temperature. Much of this warming occurred abruptly in 1987/1988. For brown trout populations, the warming resulted in an upward shift in thermal habitat that was accelerated by an increase in the incidence of temperature-dependent Proliferative Kidney Disease at the habitat's lower boundary. Because physical barriers restrict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
354
2
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 370 publications
(380 citation statements)
references
References 47 publications
11
354
2
13
Order By: Relevance
“…Recent studies have shown that air temperature in the alpine regions is changing more rapidly than in other regions of the northern hemisphere and the global average (Lebensministerium 2003;Beniston 2006;Hari et al 2006). From data analyses of twelve stations in Switzerland in the period 1864-2000, Begert et al (2005) found a rise in temperature by 1.1°C and 0.6°C per century in northern and southern side of the Alps, respectively, (Table 1) and the warming occurred mainly during autumn and winter months.…”
Section: Consequences Of Changes In Air Temperaturementioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that air temperature in the alpine regions is changing more rapidly than in other regions of the northern hemisphere and the global average (Lebensministerium 2003;Beniston 2006;Hari et al 2006). From data analyses of twelve stations in Switzerland in the period 1864-2000, Begert et al (2005) found a rise in temperature by 1.1°C and 0.6°C per century in northern and southern side of the Alps, respectively, (Table 1) and the warming occurred mainly during autumn and winter months.…”
Section: Consequences Of Changes In Air Temperaturementioning
confidence: 99%
“…However, more recently , changes in air temperatures occurred in spring and summer at lower altitude stations (<700 m a.s.l. ; Hari et al 2006). Rising air temperature is reflected in coherent rise in water temperatures (up to +1.1°C) in streams both in the lowlands and in the foothills of the Alps, but the changes are less obvious in alpine streams influenced by glaciers and/or hydropower stations (Hari et al 2006;Matulla et al 2007).…”
Section: Consequences Of Changes In Air Temperaturementioning
confidence: 99%
See 3 more Smart Citations